Kinetics of ozone decomposition in porous In2O3 monoliths. Issue 16 (23rd March 2017) - Klawinski, Danielle; Weinberger, Christian; Klaus, Dominik; Smått, Jan-Henrik; Tiemann, Michael; Wagner, Thorsten
Abstract : We determine ozone decomposition on indium oxide by utilizing the gas transducing properties of hierarchically porous monoliths. Abstract : The performance of many chemical gas-phase reactions is strongly influenced by the interaction of reactants with interfaces. Nanoporous materials, which exhibit pore diameters up to 100 nm and high specific surface areas, can be utilized to reduce the amount of cost-intensive materials ( e.g. noble metals). However, due to limitations in material transport and reaction kinetics detailed knowledge of the diffusion and the kinetics of a chemical reaction is necessary to improve the performance of chemical processes in industry and research. To experimentally study the diffusion and reaction kinetics of gaseous species inside such pores, the chemoresistive behavior of certain metal oxides such as In2 O3 can be utilized. In this work, we present a model system based on hierarchically porous monolithic indium oxide (In2 O3 ) which allows the determination of kinetic effects by utilizing its gas transducing properties. The experimental data obtained by electrical measurements are compared to two diffusion and diffusion–reaction models. Using these methods, the rate constant of ozone decomposition in porous In2 O3 is estimated. The results are the basis for a suitable material design for semiconducting gas sensors, on the nano-, meso- and macroscale, which helps in understanding the underlying mechanisms of diffusion and reaction.